2015
DOI: 10.1039/c5dt02088c
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid-catalyzed 1,2-fluorine migration with fluoroepoxides

Abstract: A catalytic 1,2-fluorine migration reaction with simple fluoroepoxides at room temperature is reported. Under Brønsted acid catalysis, α-fluorinated ketones are efficiently constructed in the absence of an external fluorine source through a 1,2-fluorine migration reaction. The experimental results indicate that the present 1,2-fluorine migration reaction proceeds via a carbocation intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Being the most electronegative atom in the periodic table, fluorine may migrate as a F – ion, a possibility that may direct the elucidation of mechanistic pathways in the reductive degradation of these compounds. Investigations of 1,2-F rearrangements in organic reactions suggest that fluorine can rearrange with a variety of charge and spin profiles, for example, through carbocation and radical intermediates in fluoroepoxides , and in complicated sequences involving multiple steps for fluorine atoms on aromatic rings . To investigate the nature of migrating fluorine, partial atomic charges and total spin densities were obtained by analyzing the SCF electron spin density and electrostatic potentials, shown in Figure , for various geometries through rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Being the most electronegative atom in the periodic table, fluorine may migrate as a F – ion, a possibility that may direct the elucidation of mechanistic pathways in the reductive degradation of these compounds. Investigations of 1,2-F rearrangements in organic reactions suggest that fluorine can rearrange with a variety of charge and spin profiles, for example, through carbocation and radical intermediates in fluoroepoxides , and in complicated sequences involving multiple steps for fluorine atoms on aromatic rings . To investigate the nature of migrating fluorine, partial atomic charges and total spin densities were obtained by analyzing the SCF electron spin density and electrostatic potentials, shown in Figure , for various geometries through rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…During this study, the authors demonstrated that these fluoroepoxides could underwent Lewis or Brønsted acid‐catalyzed rearrangement to be converted into the corresponding α‐fluoroketone derivatives. In 2015, the same group reported a slightly modified purification procedure (PTLC rather than flash chromatography) to access a larger range of fluoroepoxides [79b] . The authors noticed that the stability of the products is closely related to the electronic nature of the substituents present on the aromatic ring of the ketones.…”
Section: Fluoro‐ Monofluoromethyl‐ and Trifluoromethyl‐substituted mentioning
confidence: 99%
“…Representative addition‐cyclization reactions involve the reaction of carbonyl electrophiles with either Br 2 CFCOOEt, [22] α‐fluorosulfoximines, [23] diarylfluoromethylsulfonium salts, [24] or in situ generated LiCHIF, [25] providing access to α‐H, α‐COOEt, and α‐alkyl substituted α‐fluoroepoxides. In contrast, α‐aryl variants are not reported through addition‐cyclization sequences, despite their potential conversion to either organofluorides with one or more stereogenic centers [26] or α‐fluorinated ketones [16] . More broadly, Darzens‐type reactions are used to form epoxides from deprotonated α‐halo carbonyls, where the leaving group is either chloride or bromide [27] .…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Of particular note is that, in addition to epoxide ring-expansion reactions, [15] fluoroepoxides can also undergo fluorine migration reactions upon ring opening. [16,17] Epoxide ring-expansion/migration reactions are useful reaction sequences used in drug discovery to build molecular complexity from relatively simple precursors. [18,19] α-Fluoroepoxides are currently prepared by: 1) oxygenation of vinyl fluorides, [20] 2) fluoride substitution of halogenated epoxides, [21] and 3) addition-cyclization reactions from carbonyl electrophiles (Figure 1ai).…”
Section: Introductionmentioning
confidence: 99%